Psychometric properties of multigroup ethnic identity measure (MEIM) scores with Australian adolescents from diverse ethnocultural groups - Dandy, J.; Durkin, K.; McEvoy, Peter; Barber, B.; Houghton, S. (Academic Press, 2008)
The present study investigated the reliability and factor structure of scores on a 12-item version ofPhinney’s multigroup ethnic identity measure with an Australian sample from diverse culturalbackgrounds. Participants were 485 students aged between 10 and 15 years. The results generallysupported the reliability of the ethnic identity scale scores and suggested a two-factor structure of ethnic identity consisting of Affirmation/Belonging, and Exploration. Results concerning the other grouporientation scale were mixed. Scores for this scale showed lower internal reliability and its inclusion inconfirmatory factor analysis models with the ethnic identity scale showed only mediocre fit.Recommendations for future research include further investigations of the factor structure within ethnicidentity as derived from social identity and developmental perspectives.